Synthesis, characterization and performance of new 1,4-diazabicyclo[2.2.2]octane derivatives in anion exchange membranes - Coppola, Roxana Elisabeth (2023)
Anion exchange membranes have aroused much interest for use in electrolyzers and alkaline fuel cells. In this work, two double-charged anion exchange membranes based on poly(2,5-benzimidazole) and poly(vinylbenzyl chloride) prepared by the casting method are reported. The effect of two different quaternizing agents based on 1,4-diazabicyclo[2.2.2]octane (DABCO) was evaluated. These membranes were characterized by means of Fourier transform infrared spectroscopy, SEM, TGA, water contact angle, swelling ratio, KOH and water uptake, ionic exchange capacity and ionic conductivity. The results showed that the length of the alkyl chain has a strong effect on the membrane properties. A good performance in a zero-gap water alkaline electrolyzer was obtained for the membrane based on the butyl derivate of DABCO (BDABCO).